Hedging with Mispriced Futures - Merrick, John J. (Journal of Financial and Quantitative Analysis, 1988)
This paper analyzes the correspondence between arbitrage sector pricing efficiency and the short-term hedging costs and effectiveness of futures contracts. Reversals of initial contract mispricings by arbitrage sector trading leads to an important mispricing retum component in the total retum to hedge portfolios. The existence of the mispricing retum has implications for initial hedge ratio selection, hedging effectiveness, and expected hedge retum. The analysis is used to interpret the hedge ratio guidance and performance of short-term hedges between the Standard and Poor's 500 stock index futures contract and the underlying S&P 500 cash stock index portfolio over the 1982-1986 period.